Crucial Images in the Presentation of a Kurdish National Identity - Halil Ibrahim Yenigün (International Institute of Islamic Thought, 2005)
This book is primarily a history of the early Kurdish movement, from its inception in the late nineteenth century to the 1930s. Yet, its distinctiveness comes not from the Kurdish nationalists’ more publicized products, but from its focus on the margins of their literary attempts. This study of failed nationalism “is concerned less with how and why Kurdish nationalism did or did not ‘catch on’ than with the efforts made by [the] Kurdish elite to construct a viable concept of Kurdish identity” (p. 1). In other words, the author’s main concern is to identify how images of the Kurds were constructed and represented, and how they evolved, over time, until the late 1930s. The book is divided into three parts, each of which corresponds to a different period that delineates differing self-images of the Kurds. Each part, in turn, consists of six to eight chapters that provide an account of both key events in the Kurdish movement’s history and literary works. Part 1, “‘Awakening’ the Kurds,” deals with the movement’s background context and early period by discussing its leaders, several publications, and organizations. In this period, the Kurds’ self-definition was predominantly negative, and obstacles to modernization abounded: tribal structures, a nomadic way of life, illiteracy, ignorance, and wildness. Yet the Turks were never the “inimical other,” except for such people as the Ottoman sultan Abdulhamid and “a long line of Ottoman despots.” They had a long list of prescriptions to awaken and literally “remake” the Kurds so that they could be accepted by the nations of the civilized world. When the Wilsonian principles granted their right to self-determination without this cultural leap, some Kurds wanted a Kurdish state. However, the vast majority mourned for the Treaty of Sevrés along with their Turkish brethren, despite the fact that its articles established Kurdistan. This chapter also describes how most Kurds joined forces with the Kemalists to drive out the occupiers, only to be frustrated by the Kemalists’ subsequent assimilation projects ...